Molecular characterization of Extended Spectrum β-lactamases and AmpC β-lactamases of Escherichia coli isolates from patients treated at Maharaj Nakorn Chiang Mai Hospital - พิชญา ตันตระกูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The overuse and misuse of antibiotics have contributed to the emergence of antibiotic resistance. Escherichia coli strains resistant to the widely used extended spectrum cephalosporins have emerged worldwide and the production of extended spectrum β-lactamases (ESBLs) and AmpC β-lactamases are the major mechanisms of resistance. The aim of this study was to investigate correlation between the minimal inhibitory concentration (MIC) of two extended spectrum cephalosporins, cefotaxime and ceftazidime, among ESBL producers and the presence of specific β-lactamase (bla) genes. The MICs of cefotaxime and ceftazidime for ESBL producers were determined using agar dilution method. These ESBL producers are more resistant to cefotaxime than to ceftazidime. The presence of various bla genes in 182 clinical isolates were detected using multiplex PCR. ESBL genes were found in 172 isolates (94.5%) and AmpC β-lactamase gene was observed in 1 isolate (0.5%) whereas 9 isolates (4.9%) were found to have both ESBL and AmpC β-lactamase genes. The blaTEM + blaCTX-M-1 subgroup was the most frequent gene combination, found in 64 (35.2%) isolates. Levels of resistance to cefotaxime and ceftazidime do not depend on the accumulating number of genes but relate to type of β-lactamase gene. The presence of blaCTX-M-1subgroup was significantly correlated with the resistance to both ceftotaxime (p-value = 0.037) and ceftazidime (p-value = 0.000) suggesting that blaCTX-M-1subgroup gene might be used to predict the resistance to cefotaxime and ceftazidime of ESBL producing E. coli.